THE ROLE AND IMPROVEMENT DIRECTIONS OF DIGITAL MARKETING STRATEGIES IN INCREASING THE COMPETITIVENESS OF ENTERPRISES - Mirzohid Tuyuratovich Amonov (The Conference Hub, 2025)
This article explores the role of digital marketing strategies in enhancing the competitiveness of enterprises and proposes directions for their improvement. In today’s rapidly evolving business environment, digital tools have become critical in achieving sustainable growth and competitive advantage. The study focuses on small and medium-sized enterprises (SMEs) in Uzbekistan and applies a comprehensive methodological approach, including surveys, content analysis, SWOT analysis, and correlation techniques. Results indicate that companies using digital marketing tools—such as SEO, SMM, email marketing, CRM systems, and targeted advertising—report significant improvements in brand awareness, sales volume, customer loyalty, and operational efficiency. The study also identifies regional disparities in digital adoption, highlighting the need for government support, infrastructure development, and digital literacy training. The research concludes that strategic and systematic integration of digital marketing into business processes is not merely an option, but a necessity for ensuring long-term success in the modern competitive market.
Keywords: Digital marketing, competitiveness, small and medium enterprises, SEO, SMM, CRM, customer loyalty, Uzbekistan, digital strategy, targeted advertising.